Understanding small NGOs’ access to and use of geological data and expertise in delivering SDG 6 in eastern Africa - Wagaba, Brenda; Sayan, Caner; Haemmerli, Hannah; Gill, Joel; Parker, Alison (IWA Publishing, 2023)
Groundwater resources have the potential to meet the water demands of vulnerable communities in eastern Africa. To ensure such groundwater resources are managed sustainably, robust geological knowledge must be available and utilised by those managing groundwater. Small NGOs are one type of practitioner working on water-related projects with remote and vulnerable communities. This study aimed to understand the access to and use of geological data and expertise by small NGOs involved in water-related projects, through an online survey and key-informant interviews. The study revealed that small NGOS want to use geological data but bureaucracy makes it difficult to access free, existing government geological data sources, and that datasets are not always stored appropriately. Funding constraints hinder the ability of small NGOs to access quality geological data from other sources and to hire appropriate expertise. Donors' lack of understanding of the value of geological data affects the ability of small NGOs to budget for and include the time needed to collect or access geological data. There is a need to recognise these barriers to the usability and accessibility of geological data and expertise by key actors working on water challenges, such as small NGOs, and take steps to address them.
Keywords: eastern Africa; geological data; groundwater; hydrogeology; knowledge; NGOs